2019
DOI: 10.1029/2018jg004687
|View full text |Cite
|
Sign up to set email alerts
|

Linking Remote Sensing and Dendrochronology to Quantify Climate‐Induced Shifts in High‐Elevation Forests Over Space and Time

Abstract: It is well known that tree growth is strongly affected by climate at high elevations, but it is still unclear how climate variability influences the distribution of montane forest ecosystems, particularly tree line species. To advance knowledge in this field, we combined temporal (tree ring measurements) and spatial data (remotely sensed variables), to quantify how forests responded to climatic variability across altitudinal gradients in Central Mexico. Normalized difference vegetation index (NDVI), tree‐ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 90 publications
0
44
0
6
Order By: Relevance
“…This phenomenon was accentuated during summer 2011 when trees were under the most extreme VPD and temperature for the studied period. We also found that previous winter conditions (e.g., higher precipitation and warmer temperatures) can affect the isotopic signature of any given annual tree ring because the next growing season carries some of the photosynthetic materials from the previous year for early growth (Correa‐Díaz et al, 2019). Regarding spatial position, we found that δ 13 C ratios were less sensitive to previous climatic conditions at high elevations (south aspect) than middle elevation range or lower forest limit that agrees with Wu et al (2015) analysis (Table S3).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This phenomenon was accentuated during summer 2011 when trees were under the most extreme VPD and temperature for the studied period. We also found that previous winter conditions (e.g., higher precipitation and warmer temperatures) can affect the isotopic signature of any given annual tree ring because the next growing season carries some of the photosynthetic materials from the previous year for early growth (Correa‐Díaz et al, 2019). Regarding spatial position, we found that δ 13 C ratios were less sensitive to previous climatic conditions at high elevations (south aspect) than middle elevation range or lower forest limit that agrees with Wu et al (2015) analysis (Table S3).…”
Section: Discussionmentioning
confidence: 75%
“…As a general overview across the entire chronology (1866–2016), low‐elevation sites (3500‐NW and 3500‐SW) have historically exhibited the highest average productivity, expressed as annual basal area increments (BAI), which until recently was up to four times higher than BAIs at high‐elevation sites (3900‐NW and 3900‐SW) (see Figure 8a and Correa‐Díaz et al (2019) for further information). However, changes in physiological performance (described above) led to a progressive downward trend in BAI since the mid‐20th century, which changed those historic site differences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations